Corrosion and corrosion protection handbook - Schweitzer, Philip A. (Corrosion technology (New York, N.Y.), 1989)
Continuing to provide excellent, state-of-the-art information on corrosion and practical solutions for reducing corrosion, the second edition contains valuable suggestions on how to select the best construction material for a specific application, choose an appropriate initial design to avoid inherent corrosion pitfalls, determine what corrosion problems may exist or develop, as well as the possible extent of the problems and extablish practices to monitor corrosion of existing equipment.